Heart Transplantation, Either Alone or Combined With Liver and Kidney, a Viable Treatment Option for Selected Patients With Severe Cardiac Amyloidosis. Issue 7 (17th June 2022) - Guendouz, Soulef; Grimbert, Philippe; Radu, Costin; Cherqui, Daniel; Salloum, Chady; Mongardon, Nicolas; Maghrebi, Sami; Belhadj, Karim; Le Bras, Fabien; Teiger, Emmanuel; Couetil, Jean-Paul; Balan, Adriana; et al.
Abstract : Background: Heart transplantation in cardiac amyloidosis (CA) patients is possible and generally considered for transplantation if other organs are not affected. In this study, we aimed to describe and assess outcome in patients following heart transplantations at our CA referral center. Methods: We assessed all CA patients that had heart transplantations at our center between 2005 and 2018. Patients with New York Heart Association status 3 out of 4, with poor short-term prognosis due to heart failure, despite treatment, and without multiple myeloma, systemic disease, severe neuropathic/digestive comorbidities, cancer, or worsening infections were eligible for transplantation. Hearts were transplanted by bicaval technique. Standard induction and immunosuppressive therapies were used. Survival outcome of CA patients after transplantation was compared with recipients with nonamyloid pathologies in France. Results: Between 2005 and 2018, 23 CA patients had heart transplants: 17 (74%) had light chain (light chain amyloidosis [AL]) and 6 (26%) had hereditary transthyretin (hereditary transthyretin amyloidosis [ATTRv]) CA. Also, 13 (57%) were male, and the mean age at diagnosis was 56.5 y (range, 47.7–62.8). Among AL patients, 13 had heart-only and 5 had heart-kidney transplantations. Among ATTRv patients, 1 had heart-only and 5 had heart-liver transplantations. The 1-y survival rate after transplantation was 78%, 70% with AL, and 100% with ATTRv. At 2 y, 74% were alive: 65% with AL and 100% with ATTRv. Conclusion: After heart transplantation, French CA and nonamyloid patients have similar survival outcomes. Among CA patients, ATTRv patients have better prognosis than those with AL, possibly due to the combined heart-liver transplantation. Selected CA patients should be considered for heart transplantations.